Absent Apologies. Issue 1 (2nd January 2016) - Drew, Paul; Hepburn, Alexa
Abstract : Absent apologies—apologies that were expected but are not forthcoming—are quite frequently identified and commented on, for instance in the media. In this article we discuss two kinds of evidence that apologies can be noticeably absent for participants in ordinary interactions. The first kind is the delays that can occur in the progressivity in talk until an apology is forthcoming, particularly in cases where interlocutors are misaligned about culpability for a transgression. Such cases typically involve pursuit of an appropriate apology (admission) and an account for the other's (mis)conduct. The second kind of evidence is that where speakers fail to apologize for a putative transgression, their interlocutors can nevertheless treat the other's prior turn as though it had been an apology by absolving them of culpability in the standard way (e.g., 'that's alright'). We show that such absolution can occur irrespective of whether culpability is admitted and an apology proffered.